Unraveling Photocatalytic Mechanism and Selectivity in PET‐RAFT Polymerization. Issue 6 (15th April 2019) - Seal, Prasenjit; Xu, Jiangtao; De Luca, Sergio; Boyer, Cyrille; Smith, Sean C.
Abstract: The photoredox catalysts pheophorbide a (PheoA) and zinc tetraphenylporphine (ZnTPP) under illumination display strong selectivity toward reversible addition–fragmentation chain transfer (RAFT) agents containing thiocarbonylthio groups, namely dithiobenzoates, xanthates, and trithiocarbonates. The underlying mechanism for the process—whether via energy or electron transfer from the photoexcited catalyst to RAFT agent—has remained unclear, as has the reason for the remarkable selectivity. Quantum chemistry and molecular dynamics calculations are utilized to provide strong evidence that none of the common energy‐transfer mechanisms (Förster resonance energy transfer; Dexter electron exchange; or internal conversion followed by vibrational energy transfer) are likely to facilitate polymerization, let alone explain the observed selectivities. In contrast, extensive quantum chemical characterizations of the excited‐state orbitals associated with the catalyst–RAFT agent complexes uncover a clear selectivity pattern associated with charge‐transfer states that is highly consistent with experimental findings. The results shed light on the intrinsic catalytic role of the photocatalysts and provide a strong indication that a reversible electron/charge‐transfer mechanism underpins the remarkable photocatalytic selectivity. Abstract : A foundation for understanding the strong selectivity of photoredox catalysts, PheoA and ZnTPP, toward RAFT agents containing thiocarbonylthio groups is presented. This in turn is successfully used to report and design controlled polymeric architectures, thereby opening up new avenues toward polymer synthesis with monomer sequences, tailored for different applications.